WAKAF TUNAI - A Zaenurrosyid (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2013)
Waqf as the way to worship Allah is also as a great potential asset for moslem. This great potential is empowered by various management innovation. Cash Wakaf that has been developed in several countries, in fact, be able to strengthen the economics of Moslem society. In the perspective of Moslem scholars”, not all of them agree with cash waqf. Although there is a different opinion about cash waqf, the majority of them legalized it. Either Hanafi or Maliki legalized cash waqf. Furthermore Hambali Moslem scholar also accept cash waqf and the other is not, while mazhab Syafi’iyah generally does not allow the practice of cash waqf. In the context of Indonesian Law. Law number 41, 2004 legalizes cash waqf, or valuable letter. This article discusses and analyzes cash waqf management at PPPA (The program for children who learn Quran by heart) with the analysis from the perspective of Islamic law and positive law No. 41, 2004. Based on the result of the research, it can be stated that cash money management at PPPA has been relevant with both of the approach of the law, and those developed cash waqf programs included educational institution, health, religion, and society needs services, that recently can reach hundreds of billions.